A mixture proportioning method for the development of performance-based alkali-activated slag-based concrete. (October 2018) - Li, Ning; Shi, Caijun; Zhang, Zuhua; Zhu, Deju; Hwang, Hyeon-Jong; Zhu, Yuhan; Sun, Tengjiao
Abstract: This paper reports a general mixture design procedure for alkali-activated slag concrete, which is an essential step towards industrial application. The procedure involves three steps: 1) the determination of coarse and fine aggregate ratio according to close packing model; 2) the determination of liquid phase (water content and activator) based on compressive strength; and 3) the determination of excess paste content by workability requirement and measurement. Effects of mixture proportional factors, including activator composition, water content, fly ash content, and binder/aggregate ratio are examined on consistency, setting time and compressive strength. The relationship between performance and precursor composition is established using simplex centroid design method. Using the mixture proportioning method, alkali-activated concretes with compressive strength grades of C40, C60, and C80 are successfully prepared with initial setting time of 1–3 h and slump of more than 200 mm.